2008
DOI: 10.1128/iai.01253-07
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Moraxella catarrhalis Genome: Identification of Potential Vaccine Antigens Expressed during Human Infection

Abstract: Moraxella catarrhalis is an important cause of respiratory infections in adults and otitis media in children.Developing an effective vaccine would reduce the morbidity, mortality, and costs associated with such infections. An unfinished genome sequence of a strain of M. catarrhalis available in the GenBank database was analyzed, and open reading frames predicted to encode potential vaccine candidates were identified. Three genes encoding proteins having molecular masses of approximately 22, 75, and 78 kDa (des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 49 publications
(52 reference statements)
2
63
0
Order By: Relevance
“…Further, it has been suggested that the production of ␤-lactamases by M. catarrhalis could protect cocolonizing pathogens from the effects of ␤-lactam antibiotic treatment (24,71). In any case, the financial impact on global health care systems of the high incidence of M. catarrhalis colonization and disease is significant, and consequently, several research groups are currently involved in identifying and assessing the usefulness of putative M. catarrhalis vaccine candidates (91,122,144,155). …”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been suggested that the production of ␤-lactamases by M. catarrhalis could protect cocolonizing pathogens from the effects of ␤-lactam antibiotic treatment (24,71). In any case, the financial impact on global health care systems of the high incidence of M. catarrhalis colonization and disease is significant, and consequently, several research groups are currently involved in identifying and assessing the usefulness of putative M. catarrhalis vaccine candidates (91,122,144,155). …”
Section: Introductionmentioning
confidence: 99%
“…MID is an outer-membrane protein (OMP) with specific affinity for soluble and cell-bound human IgD and is the only IgDbinding protein in Moraxella (Forsgren et al, 2001). Several other virulence-associated genes have been identified that may be associated with colonization and infection of M. catarrhalis, including the OMPs CopB, OMPCD, McaP, MhaB, MhaC, Msp22, Msp75, Msp78 and lipooligosaccharide (LOS) Balder et al, 2007;Lipski et al, 2007;Liu et al, 2007;Riesbeck et al, 2006;Ruckdeschel et al, 2008Ruckdeschel et al, , 2009Tan et al, 2006a). Furthermore, several of these virulence genes have also been associated with the induction of the humoral immune response, making them potential vaccine candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…UspA1 and UspA2 acquire their adherence characteristics through multifunctional binding sites, which include domains that have the ability to attach to epithelial cells via cell-associated fibronectin, laminin and vitronectin (Tan et al, 2006b). Furthermore, UspA1 includes a critical binding site for carcinoembryonic antigen-related cell adhesion molecules, which are expressed in various human tissues including respiratory epithelia (Hill & Virji, 2003;Slevogt et al, 2008 Balder et al, 2007;Lipski et al, 2007;Liu et al, 2007;Riesbeck et al, 2006;Ruckdeschel et al, 2008Ruckdeschel et al, , 2009Tan et al, 2006a). Furthermore, several of these virulence genes have also been associated with the induction of the humoral immune response, making them potential vaccine candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several adhesin molecules with different specificities for host cell receptors have been identified, and these are potentially appealing vaccine antigens since adherence to the respiratory epithelium is a critical step in the pathogenesis of infection. A genome-mining approach has identified novel candidate antigens and has the potential to identify many more [26]. No writing assistance was utilized in the production of this manuscript.…”
Section: Vaccine Antigensmentioning
confidence: 99%